2017
DOI: 10.1007/978-3-319-68059-0_18
|View full text |Cite
|
Sign up to set email alerts
|

How Real Is Unreal?

Abstract: Abstract. As a consequence of prolonged muscle contraction, acute pain arises during exercise due to a build-up of noxious biochemicals in and around the muscle. Specific visual cues, e.g., the size of the object in weight lifting exercises, may reduce acute pain experienced during exercise. In this study, we examined how Virtual Reality (VR) can facilitate this "material-weight illusion", influencing perception of task difficulty, which may reduce perceived pain. We found that when vision understated the real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…The findings also revealed lower levels of the perceived difficulty in the rehabilitation exercise performance during the VR session in comparison ratings of conventional rehabilitation. The findings are in line with a study that suggested that VR can influence positively the perception of task difficulty during upper limb muscle contraction (Matsangidou et al 2017a, b). To examine this, participants were asked to hold their Baseline Mass in an isometric contraction for as long as they could with their elbow at an angle of 90º flexion.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings also revealed lower levels of the perceived difficulty in the rehabilitation exercise performance during the VR session in comparison ratings of conventional rehabilitation. The findings are in line with a study that suggested that VR can influence positively the perception of task difficulty during upper limb muscle contraction (Matsangidou et al 2017a, b). To examine this, participants were asked to hold their Baseline Mass in an isometric contraction for as long as they could with their elbow at an angle of 90º flexion.…”
Section: Discussionsupporting
confidence: 86%
“…In recent decades, computer technology has brought to light new opportunities for pain management in painful therapeutic processes (Chau et al 2020;Furness et al 2019;Phelan et al 2019). Virtual reality (VR) is a representative example of this type of technology since it allows users to experience a computer-simulated reality with visual, auditory, tactile and olfactory interactions (Ma and Zheng 2011) which results in distracting the patient from perceiving nociceptive signals and pain (Matsangidou et al 2017a, b ). VR for pain management has been introduced in the research community as VR-analgesia and it appears to be an advanced form of analgesia caused by conventional distraction (Hoffman et al 2004;Schmitt et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the programmed complexity, the user can immerse in the virtual world by looking around, walking through, manipulating objects or performing a series of actions (Weiss, Kizony, Feintuch, & Katz, 2006). VR has been successfully used therapeutically, including pain management, physical rehabilitation and psychotherapy (Matsangidou, Ang, & Sakel, 2017;Matsangidou, Ang, Mauger, Otkhmezuri, & Tabbaa, 2017;Morris, Louw, & Grimmer-Somers, 2009;Riva, 2005), and for phobias (Rothbaum et al, 1995).…”
Section: Bringing the Outside In: The Feasibility Of Virtual Reality mentioning
confidence: 99%
“…VR as a technology has been also used to improve physical training in healthy adults and athletes with promising results [27][28][29]. In general, most of the research related to VR and dementia focuses on the enhancement of specific skills which tend to decline within the course of the condition.…”
Section: Related Workmentioning
confidence: 99%